The Construct Validity of the Dutch Personality Inventory for DSM-5 Personality Disorders (PID-5) in a Clinical Sample. (February 2016) - Bastiaens, Tim; Claes, Laurence; Smits, Dirk; De Clercq, Barbara; De Fruyt, Filip; Rossi, Gina; Vanwalleghem, Dominique; Vermote, Rudi; Lowyck, Benedicte; Claes, Stephan; De Hert, Marc
The factor structure and the convergent validity of the Personality Inventory for DSM-5 (PID-5), a self-report questionnaire designed to measure personality pathology as advocated in the fifth edition, Section III of Diagnostic and Statistical Manual of Mental Disorders ( DSM-5 ), are already demonstrated in general population samples, but need replication in clinical samples. In 240 Flemish inpatients, we examined the factor structure of the PID-5 by means of exploratory structural equation modeling. Additionally, we investigated differences in PID-5 higher order domain scores according to gender, age and educational level, and explored convergent and discriminant validity by relating the PID-5 with the Dimensional Assessment of Personality Pathology—Basic Questionnaire and by comparing PID-5 scores of inpatients with and without a DSM-IV categorical personality disorder diagnosis. Our results confirmed the original five-factor structure of the PID-5. The reliability and the convergent and discriminant validity of the PID-5 proved to be adequate. Implications for future research are discussed.